Marketing Strategy of Geopark Ciletuh Palabuhanratu Tourist Attraction - Rahmawati, Yuli Diani; Rahayu, Agus; Dirgantari, Puspo Dewi; Nandi, Nandi (Indonesia University of Education, 2021)
West Java is a province that has many mainstay tourist attractions in Indonesia. Sukabumi is a district in West Java that has one of the tourist attractions that has been inaugurated as a part of the UNESCO Global Geopark Network (UGGN) in 2018, this area opens the opportunity to become a leading destination in West Java and even nationally. The tourist attraction of the Ciletuh Palabuhanratu Geopark offers natural and cultural attractions that can be explored in geological diversity, biological diversity, and cultural diversity. The number of tourists visiting the Ciletuh Palabuhanratu Geopark Tourist Attraction has increased from 2012-2018, but in 2019 the number has decreased. This study aims to analyze the tourism marketing strategy carried out by the manager to increase the number of tourist visits to the Ciletuh Palabuhanratu Geopark. The method used is qualitative, data collection through literature study, interviews, and observation. The data obtained were analyzed descriptively. To analyze the marketing mix and strategy using a SWOT analysis, which aims to identify the strategies needed to increase tourism visits. The results showed that the marketing strategy can be done to increase the number of tourists through the SWOT approach. The SO strategy, namely the strategy of packaging attractive tourism products and services, the ST strategy through the strategy of instilling a brand image in the minds of visitors / Building a place identity (Positioning), the WO strategy, namely through the promotion strategy, the WT strategy, namely through the community empowerment strategy and building commitment and cooperation with a stakeholder.